(untitled) (Encuentros, 2024)
Video politics has been studied from the perspective of Political Science, focusing on verbal discourse and its methods of persuasion, neglecting the structural analysis of audiovisual elements. In this article, derived from a doctoral research, a methodology is proposed that combines film analysis theory, digital communication, and functional discourse theory to analyze digital video political pieces. Through hermeneutic research with a literature review, categories and variables were established, creating a codebook with audiovisual, narrative, and typological characteristics of the pieces. The methodology was tested on 175 pieces and resulted in a method that systematizes audiovisual, narrative, and typological components. Furthermore, it allows for representing the pieces as replicable structural models and comparing their interaction on social platforms.